2022
DOI: 10.1111/mcn.13374
|View full text |Cite
|
Sign up to set email alerts
|

Do changes in women's household status in Nepal improve access to food and nutrition?

Abstract: Women's nutritional status remains poor in South Asia, impacting maternal and infant health outcomes. Women's household status is also low, as evidenced by eating behaviours. We started with triadic qualitative interviews with newly married women, husbands and mothers‐in‐law to explore the link between women's status and eating patterns, followed by longitudinal data from a cohort of 200 newly married women in rural Nepal to measure associations over time. Quantitative data were collected every 6 months for 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…We found that newly married women and girls in particular had their decision-making restricted, as they have not yet gained status through their reproductive role. However, quantitative evidence from Nepal and Bangladesh suggests that the household status of women and girls does not increase with time or with the delivery of a child [131][132][133][134]. These nuances are context-specific and difficult to measure, requiring research at a local level, which we were unable to undertake in this regional review [135].…”
Section: Discussionmentioning
confidence: 99%
“…We found that newly married women and girls in particular had their decision-making restricted, as they have not yet gained status through their reproductive role. However, quantitative evidence from Nepal and Bangladesh suggests that the household status of women and girls does not increase with time or with the delivery of a child [131][132][133][134]. These nuances are context-specific and difficult to measure, requiring research at a local level, which we were unable to undertake in this regional review [135].…”
Section: Discussionmentioning
confidence: 99%
“…• The low status of women and harmful gender norms place them in situations that are detrimental to their mental health and well-being. likelihood of eating last in the household (Diamond Smith et al, 2022). Another qualitative study from Nepal also found that even when women became pregnant, women continued to conform to these gendered norms of eating last in the household to show deference to elders (Morrison et al, 2021).…”
Section: Key Points/highlightsmentioning
confidence: 94%
“…However, this might change as newly married women gain status in the household––as women go out to work, get pregnant, or have children. A recent study of newly married women observed that there was no significant association between becoming pregnant and eating last but working outside the home was associated with a lower likelihood of eating last in the household (Diamond Smith et al, 2022 ). Another qualitative study from Nepal also found that even when women became pregnant, women continued to conform to these gendered norms of eating last in the household to show deference to elders (Morrison et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, market access does not always lead to better nutritional outcomes (Moe, 2002;Nandi et al, 2021;Usman and Callo-Concha, 2021). Similarly, as established in the intra-household decision-making literature, control and ownership of household income and assets tend to influence crop sales and nutrition outcomes (Diamond-Smith et al, 2022;Kulkarni et al, 2021).…”
Section: Related Literaturementioning
confidence: 97%